CSVS, a crowdsourcing database of the Spanish population genetic variability. Issue Volume 49:Issue D1(2021) (29th September 2020) - Peña-Chilet, María; Roldán, Gema; Perez-Florido, Javier; Ortuño, Francisco M; Carmona, Rosario; Aquino, Virginia; Lopez-Lopez, Daniel; Loucera, Carlos; Fernandez-Rueda, Jose L; Gallego, Asunción; García-Garcia, Francisco; González-Neira, Anna; et al.
Abstract: The knowledge of the genetic variability of the local population is of utmost importance in personalized medicine and has been revealed as a critical factor for the discovery of new disease variants. Here, we present the Collaborative Spanish Variability Server (CSVS), which currently contains more than 2000 genomes and exomes of unrelated Spanish individuals. This database has been generated in a collaborative crowdsourcing effort collecting sequencing data produced by local genomic projects and for other purposes. Sequences have been grouped by ICD10 upper categories. A web interface allows querying the database removing one or more ICD10 categories. In this way, aggregated counts of allele frequencies of the pseudo-control Spanish population can be obtained for diseases belonging to the category removed. Interestingly, in addition to pseudo-control studies, some population studies can be made, as, for example, prevalence of pharmacogenomic variants, etc. In addition, this genomic data has been used to define the first Spanish Genome Reference Panel (SGRP1.0) for imputation. This is the first local repository of variability entirely produced by a crowdsourcing effort and constitutes an example for future initiatives to characterize local variability worldwide. CSVS is also part of the GA4GH Beacon network. CSVS can be accessed at: http://csvs.babelomics.org/ .